Improving Sastra Literature in Poetry Learning Through Outdoor Learning for S-2 Elementary Education Students - Muktadir, Abdul; Ariffiando, Nady Febri (International Conference on Elementary Education, 2020)
The objectives of this research were: (1) to improve the learning process of poetry learning through outdoor learners in bachelor students (S2) at elementary education (Pendas) and (2) to Improve learning outcomes by increasing literacy in poetry learning through outdoor learning in S-2 Pendas students . This research is a class action research, with 2 cycles, each cycle consisting of planning, implementation, observation and reflection. The subjects of the study were the students at A class and B class in the first semester in the Indonesian Language Elementary Education course. The research instrument was an observation sheet and test results. Research data in the form of test data and observation data. Data analysis techniques used the average value. The results showed that outdoor learning can improve student learning processes and outcomes. Improved learning process is characterized by the involvement of teaching participants more active and enthusiastic during learning. The improvement of learning outcomes is characterized by an increase in the average value of 59,7 in the first cycle to an average value of 74.43 in cycle 2